PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK DI KELAS VIII SMP NEGERI 2 PADANG PANJANG - Suci Aisyah Putri (Departemen Matematika, 2019)
Mathematical critical thinking ability is one of the abilities that must be possessed by students in the 21st century. However, in class VIII of SMPN 2 Padang Panjang students' mathematical critical thinking ability is still low. Students only listen and receive information from the teacher, so learning becomes teacher centered. The purpose of the study was to describe the effect of the Problem Based Learning model on students 'mathematical critical thinking skills better than students' mathematical critical thinking skills by using conventional learning in class VIII of SMPN 2 Padang Panjang. This type of research is quasi-experimental and descriptive with a Randomized Control Group Only Design. The research instrument is a test of critical thinking skills. From the data analysis it was concluded that students' critical thinking skills that applied the PBL model were better than the students' critical thinking abilities who applied conventional learning, and there was an increase in students' critical thinking skills while learning to apply the PBL model. Keywords - Mathematical Critical Thinking Ability, Problem Based Learning Model, Learning Conventional